How to Get Daily Capital Gain in Covid-19 Pandemic Period? (Case study: Indonesia Stock Exchange) - Kartini Harahap (Sekolah Tinggi Manajemen IPMI, 2022)
The purpose of this research is to find out how to obtain daily capital gains in the midst of the Covid-19 pandemic using the day trade strategy and the Stochastic Oscillator as a technical indicator case study of stocks in the telecommunications industry sector. This research is descriptive in nature and uses secondary data, namely: data on daily stock prices and hourly charts, per 10 minutes on the stock price movements of PT Telekomunikasi Indonesia Tbk (TLKM) and PT Smartfren Telecom Tbk (FREN). The result of this study are finding TLKM and FREN stocks as the right stocks for day trade, day trading from the market opening or in the morning and completing transactions during the day because the volume of shares decreases reflected in the volume of TLKM shares, but not on FREN shares. Stochastic Oscillator indicator can be used to obtain daily capital gains at TLKM and FREN stocks; (a) the red box area is the best momentum for